Efektivitas Praktikum Virtual Terhadap Pemahaman Materi Sel Pada Mata Pelajaran Biologi SMA N 1 Kopang - Andre Maulana Sokib; Muhammad Bagas Prasetyo (Educational Note, 2025)
This study aims to determine the effectiveness of virtual laboratory activities in improving students’ understanding of cell material in Biology at SMA Negeri 1 Kopang. The development of educational technology provides new opportunities for implementing digital laboratory practices, particularly in the context of limited laboratory facilities and distance learning. This research employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The research subjects consisted of 60 eleventh-grade students who were divided into two groups: an experimental group that utilized virtual laboratory media and a control group that received conventional instructional methods. The instrument used was a conceptual understanding test on cell material that had been validated and tested for reliability. Data analysis using an independent samples t-test revealed a significant difference between the posttest results of the experimental group and the control group, with a p-value < 0.05. The group that participated in virtual laboratory activities demonstrated a higher improvement in conceptual understanding compared to the control group. These findings indicate that the use of virtual laboratory activities can serve as an effective alternative to enhance the quality of Biology learning, particularly for abstract topics such as cell structure and function. It is recommended that Biology teachers consider integrating digital laboratory media as part of innovative and contextual teaching strategies.